Vocational Students' Perception toward the Use of Online Instructional Media - Dini Hadiani; Nia Nuryanti Permata; Emma Dwi Ariyani (SOSHUM : Jurnal Sosial dan Humaniora, 2023)
This study aims to provide an overview of the use of instructional media during online learning from vocational higher education students' perspectives. The education system in the vocational institution focuses on practical activities, so the use of instructional media during online learning faces various problems. Online learning is believed to be effective if there is a two-way interaction between lecturers and students in class using effective instructional media. This research was conducted to look into the students' perception of using online instructional media. With a sample of 181 students, this study employed a descriptive quantitative method. Data collection was carried out by distributing questionnaires through Google Forms consisting of 17 questions with a Likert scale. In addition, semi-structured interviews with students were carried out for data triangulation. The results showed that the student perception of using instructional media during online learning is good, with an average score of 3.15 (Scale of 1- 4). The students perceived that instructional media during online learning increases their confidence and competence in learning, and their awareness of mastering a subject matter increased slightly, primarily in theoretical subjects. However, in practical classes, students still experienced problems due to the need for hands-on training. Therefore, the institution must provide a technological trend for lecturers and students, improve the teachers' competence in online instructional media, and improve software and equipment facilities that encourage and support the online learning process for more effective implementation.